Design Thinking: A Case Study on Mushroom Farming - Laurence; Agustina Christiani; Eric Jobiliong; Priskila Christine Rahayu; Silalahi, Rudy Vernando (Universitas Pelita Harapan, 2024)
In this design thinking project, observations were conducted on a white oyster mushroom cultivation business in Ciakar Village. This family-owned and self-managed business faces no issues with local demand, as confirmed through interviews with the owner, which indicates a stable target market. However, from the supply side, current production levels are insufficient to meet market demand. Business operations are largely conventional, leading to extended production times. A significant challenge is the manual preparation of mushroom growth media, which lengthens production time and limits harvest capacity. Using a human-centered design thinking approach, this project proposes a prototype solution aimed at improving production efficiency, providing a foundation for further development tailored to the business owner's needs.